Estudio de algunas alternativas de alimentación para peces en confinamiento - Sisa LLumitaxi, Carlos Nain (2022)
In aquaculture it is necessary to look for food alternatives for fish in confinement, which helps reduce production costs and therefore increases the economic benefits of fish farmers. Aquaculture nutrition faces a challenge, to implement other protein sources of plant origin with greater availability and low cost. In the studies carried out by various authors that are cited in this work. It is observed that they achieved excellent results in biological silage diets from fish residues. A diet including 30% biological silage from fish residues (To obtain silage, viscera and residues resulting from filleting were fermented by adding an inoculum of lactic acid bacteria (commercial yoghurt) and 20% cassava flour as a carbon source, presented significantly higher weight gain, size increase and feed conversion compared to the treatments evaluated, probably related to the high levels of polyunsaturated fatty acids Perea et al (2018) Other alternative ingredients used in fish farming include proteins and vegetable oils, agro-industrial by-products, aquatic plants such as Lemna and azolla, as well as vegetable protein of unicellular origin such as antibiotics and prebiotics; Llanes and Toledo 2017, refer to products and by-products of animal origin such as silage, earthworm and excreta, by-products transformed animals and fermented yeasts, as stated by González et al. l. (2017).